A nickel foam loaded silver cobalt-based monolithic catalyst and a preparation method and application thereof

By growing silver-cobalt-based active components in situ on nickel foam to form a porous structure of rolled-up nanosheets, the problems of easy aggregation and insufficient stability of active components in existing catalysts for industrial waste gas purification are solved, and the effect of low-temperature and high-efficiency purification of VOCs is achieved.

CN123038831APending Publication Date: 2026-11-06NORTHEASTERN UNIV CHINA
View PDF 1 Cites 0 Cited by

Patent Information

Application Number
CN202611554237.3
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2026-10-09
Publication Date
2026-11-06

AI Technical Summary

Technical Problem

Existing powdered and granular catalysts for industrial waste gas purification suffer from problems such as easy agglomeration of active components, low mechanical strength, limited mass transfer efficiency, high bed pressure drop, insufficient long-term stability, and poor water resistance, making it difficult to achieve efficient purification of volatile organic compounds (VOCs). In particular, the high cost of precious metal components makes large-scale promotion difficult.

Method used

Using nickel foam as a substrate, silver-cobalt-based active components are grown in situ via a hexadecyltrimethylammonium bromide-assisted hydrothermal method, forming an open porous three-dimensional structure of nanosheets. This achieves uniform anchoring and dispersion of Ag, promotes electronic synergy, and enhances catalytic activity and stability.

Benefits of technology

It significantly improves the low-temperature catalytic oxidation performance and long-term operational stability of the catalyst, has excellent resistance to water vapor interference, simplifies the preparation process and reduces costs, and is suitable for the purification of VOCs in industrial waste gas.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN123038831A_ABST
    Figure CN123038831A_ABST
Patent Text Reader

Abstract

This invention belongs to the field of catalyst preparation technology, and relates to a nickel foam-supported silver-cobalt-based monolithic catalyst, its preparation method, and its application. The catalyst comprises a three-dimensional porous nickel foam support and a silver-doped cobalt tetroxide active layer supported on the surface of the nickel foam support; wherein the active layer has an open porous, rolled-up three-dimensional structure formed by the assembly of rolled nanosheets. The preparation method involves placing clean nickel foam in a 2-methylimidazole solution to obtain a nickel foam support; preparing a homogeneous metal salt solution; placing the nickel foam support in the homogeneous solution for a hydrothermal reaction to obtain a nickel foam-supported silver-cobalt-based composite material; and then washing, drying, and calcining to obtain the nickel foam-supported silver-cobalt-based monolithic catalyst. The nickel foam-supported silver-cobalt-based monolithic catalyst prepared by this invention maintains excellent catalytic activity under high space velocity conditions, while also exhibiting outstanding resistance to water vapor interference and long-term operational stability, demonstrating excellent overall adaptability to various operating conditions.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention belongs to the field of catalyst preparation technology, and specifically relates to a nickel foam-supported silver-cobalt based monolithic catalyst, its preparation method, and its application. Background Technology

[0002] Volatile organic compounds (VOCs) are significant gaseous pollutants emitted during industrial production processes, widely originating from industries such as petrochemicals, coating and printing, electronics manufacturing, and solvent use. VOCs exhibit strong volatility and mobility, participating in photochemical reactions in the atmosphere, promoting ozone and secondary organic aerosol formation, and exacerbating regional complex air pollution. Some VOCs are highly toxic, carcinogenic, and mutagenic, and long-term exposure can pose potential harm to the human respiratory, nervous, and immune systems. Therefore, achieving efficient purification of VOCs in industrial waste gas is of great significance for improving air quality and protecting human health.

[0003] Currently, thermocatalytic oxidation technology is considered one of the most promising technologies in industrial exhaust gas purification due to its ability to convert VOCs into harmless carbon dioxide and water at relatively low temperatures. However, existing powdered catalysts still face challenges in practical industrial applications, such as easy agglomeration of active components, low mechanical strength, limited mass transfer efficiency, and difficulty in engineered packing. Furthermore, traditional granular catalysts typically suffer from high bed pressure drop, insufficient long-term operational stability, and poor water resistance under complex operating conditions, hindering their practical application in industrial waste gas purification. Therefore, developing novel monolithic VOCs catalysts with high activity, high stability, and excellent mass transfer performance will help promote the development of VOCs pollution control technologies.

[0004] In constructing efficient catalytic systems for VOCs purification in industrial waste gas, the selection and loading method of active components directly determine the performance and economy of the catalyst. While noble metal components (such as Pt and Pd) possess excellent low-temperature oxidation activity, their scarcity and high cost hinder large-scale application. Ag, as a low-cost noble metal with good catalytic activity, holds promise as an ideal alternative balancing performance and economy, if precisely morphologically controlled and supported to fully expose active sites at extremely low dosages. Although transition metal oxides are widely available and have good thermal stability, their high ignition temperatures and insufficient intrinsic activity make them a preferred strategy in the field of catalytic oxidation. Therefore, modifying non-noble metal oxides with minimal amounts of Ag, leveraging electronic synergy and interfacial effects between the two to significantly improve catalytic efficiency with almost no increase in cost, has become the preferred approach in the current catalytic oxidation field. Chinese invention patent CN119281352A discloses a cobalt-based monolithic catalyst with quenched silver loading. This technology uses cordierite ceramic as a carrier, which has a low specific surface area and limited dispersion of active components. At the same time, the silver clusters introduced by the quenching process are prone to migration and aggregation under high temperature reaction conditions. The long-term operational stability and resistance to water vapor interference are unknown, making it difficult to achieve atomic-level dispersion. There is still room for improvement in the utilization efficiency of precious metals.

[0005] Meanwhile, in the construction of monolithic catalysts, utilizing the morphology regulation effect of liquid-phase synthesis to construct a catalytic active layer on the surface of a macroscopic metal support in situ, which combines highly dispersed active components, strong interfacial bonding, and multi-level mass transfer channels, is the key to achieving a synergistic improvement in low precious metal loading, high catalytic efficiency, and long-term operational stability.

[0006] In summary, there is a lack of existing technologies for silver-cobalt-based monolithic catalytic oxidation of VOCs that can simultaneously achieve high activity and water resistance. Summary of the Invention

[0007] To address the aforementioned technical problems, this invention proposes a nickel foam-supported silver-cobalt-based monolithic catalyst, its preparation method, and its application. Hexadecyltrimethylammonium bromide is used as a morphology modifier to assist in the preparation of a cobalt-based catalyst supported on nickel foam with trace amounts of Ag doping. This method utilizes the complexation reaction between hexadecyltrimethylammonium bromide and Ag species to regulate the deposition behavior of Ag precursors, achieving uniform anchoring and high dispersion of Ag active components on the catalyst surface. This significantly improves the low-temperature catalytic oxidation performance and engineering application potential of the monolithic catalyst.

[0008] Technical means: The first aspect of this invention provides a method for preparing a nickel foam-supported silver-cobalt-based monolithic catalyst, comprising the following steps: (1) Remove the surface oxide layer from the cut nickel foam, then perform ultrasonic cleaning to obtain clean nickel foam, and dry it for later use; put the dried nickel foam into 2-methylimidazole solution and perform ultrasonic treatment to obtain nickel foam carrier. (2) AgNO3, Co(NO3)2·6H2O, urea and hexadecyltrimethylammonium bromide are dissolved together in deionized water and stirred at room temperature to form a homogeneous solution. The nickel foam support obtained in step (1) is placed in the homogeneous solution and subjected to hydrothermal reaction. After cooling to room temperature, a nickel foam-supported silver cobalt-based composite material is obtained. After washing with deionized water and drying, it is finally calcined in air atmosphere to obtain a nickel foam-supported silver cobalt-based monolithic catalyst.

[0009] Furthermore, in step (1), the nickel foam is cut to a size of 6-8 cm. 2 The surface oxide layer was removed using an HCl solution with a concentration of 0.1–0.3 mol / L, and the ultrasonic cleaning time was 5–15 min.

[0010] Furthermore, in step (1), the 2-methylimidazole solution is a transparent solution obtained by stirring and dissolving for 5 to 15 minutes, and its concentration is 0.1 to 0.5 mol / L.

[0011] Furthermore, in step (1), the ultrasonic treatment time is 20 to 40 minutes.

[0012] Furthermore, in step (2), the Ag / Co molar percentage is 2-4%, the amount of Co(NO3)2·6H2O is 2-6 mmol, the amount of urea is 0.01-0.03 mol, and the amount of hexadecyltrimethylammonium bromide is 0.8-1.5 mmol.

[0013] Furthermore, in step (2), the hydrothermal reaction temperature is 100-150℃ and the hydrothermal reaction time is 8-16h; the number of times of washing with deionized water is at least 3; the drying temperature is 60-80℃ and the drying time is 10-15h; the calcination temperature is 300-700℃ and the calcination time is 2-6h.

[0014] A second aspect of the present invention provides a nickel foam-supported silver-cobalt-based monolithic catalyst prepared by the preparation method described above, comprising: a three-dimensional porous nickel foam support and a silver-doped cobalt tetroxide active layer supported on the surface of the nickel foam support; wherein the active layer has an open porous rolled three-dimensional structure formed by the assembly of rolled nanosheets.

[0015] The third aspect of this invention proposes the application of the catalyst prepared by the above preparation method or the above catalyst in the thermocatalytic oxidation of volatile organic compounds.

[0016] The fourth aspect of this invention proposes the application of the catalyst prepared by the above preparation method or the above catalyst in the thermocatalytic oxidation of benzene.

[0017] Beneficial effects 1. Controllable catalyst morphology and fully exposed active sites: This invention uses nickel foam as a substrate and achieves in-situ growth of silver-cobalt-based active components via a hydrothermal method assisted by hexadecyltrimethylammonium bromide (CTAB). CTAB and Ag + The combination forms an AgBr precursor, achieving both uniform anchoring and atomic-level dispersion of silver species on the surface of cobalt-based oxides (Ag was not detected by XRD when Ag / Co ≤ 4%). 0 The Co3O4 nanosheets exhibit characteristic peaks and, through their surfactant properties, regulate crystal growth orientation, inducing the bending and self-assembly of open, porous, roll-like three-dimensional structures. This structure effectively prevents the aggregation of active components, fully exposes catalytic active sites, and provides efficient channels for reactant diffusion and product transport.

[0018] 2. Excellent low-temperature catalytic activity: In this invention, the electronic synergistic effect between Ag species and cobalt-based oxides promotes the activation of oxygen molecules and the formation of surface-active oxygen species, significantly enhancing the catalyst's redox capability. EPR and H2-TPR characterization results show that the optimally sized catalyst (Co-Ag4 / NF) possesses abundant oxygen vacancies and the lowest reduction peak temperature. Under harsh reaction conditions with a space velocity as high as 60,000 mL / g / h, a benzene concentration of 1000 ppm, and an O2 content of 20%, this catalyst exhibits excellent low-temperature catalytic activity. 50 Only 228℃, T 90 As low as 244°C, it outperforms the comparative catalyst without Ag (T 90 =288℃) and the comparative catalyst without CTAB (T 90 =278℃), indicating that Ag and CTAB have a significant synergistic effect on improving catalytic performance.

[0019] 3. Strong resistance to water vapor interference: The catalyst of this invention can still maintain about 90% benzene conversion rate in gas streams containing 1.5 vol% and 3 vol% water vapor, and its activity quickly recovers to the initial level after the water vapor is stopped, showing excellent water resistance and is suitable for actual working conditions in industrial waste gas containing water vapor.

[0020] 4. Outstanding long-term operational stability: The catalyst of this invention exhibits excellent long-term operational stability at T... 90 After 50 hours of continuous operation at the specified temperature, the benzene conversion rate did not decrease significantly. The active components and the nickel foam substrate were firmly bonded together through in-situ chemical bonding, with no risk of detachment, meeting the requirements for long-term industrial operation.

[0021] 5. Simple preparation process and significant cost advantage: This invention uses a one-step hydrothermal method to achieve in-situ growth of active components on nickel foam, avoiding the complex molding, coating, and bonding steps in the preparation of traditional powder catalysts, thus simplifying the process. Simultaneously, the Ag loading is extremely low (Ag / Co molar percentage less than 4%), significantly improving catalytic efficiency with almost no increase in cost, combining performance and economic advantages, and showing promising prospects for industrial application. Attached Figure Description

[0022] Figure 1 This is a stability test diagram of the catalyst prepared in Example 1 of the present invention; Figure 2 This is a water resistance test diagram of the catalyst prepared in Example 1 of the present invention; Figure 3 The X-ray diffraction patterns of the catalysts prepared in Examples 1-2 and Comparative Examples 1-2 of this invention are shown below. Figure 4 These are scanning electron microscope (SEM) images of the catalysts prepared in Examples 1-2 and Comparative Examples 1-2 of the present invention. In the images, a1 shows the low-magnification overall morphology of Comparative Example 1 (scale bar 100 μm), b1 shows the medium-magnification overall morphology of Comparative Example 1 (scale bar 5 μm), and c1 shows the high-magnification overall morphology of Comparative Example 1 (scale bar 200 nm). Similarly, a2 shows the low-magnification overall morphology of Example 2 (scale bar 100 μm), b2 shows the medium-magnification overall morphology of Example 2 (scale bar 5 μm), and c2 shows the overall morphology of Example 2... High-magnification overall morphology (scale bar 200 nm); Figure a3 shows the low-magnification overall morphology of Example 1 (scale bar 100 μm), b3 shows the medium-magnification overall morphology of Example 1 (scale bar 5 μm), and c3 shows the high-magnification overall morphology of Example 1 (scale bar 200 nm); Figure a4 shows the low-magnification overall morphology of Comparative Example 2 (scale bar 100 μm), b4 shows the medium-magnification overall morphology of Comparative Example 2 (scale bar 5 μm), and c4 shows the high-magnification overall morphology of Comparative Example 2 (scale bar 200 nm); Figure 5 The electron paramagnetic resonance spectra of the catalysts prepared in Examples 1-2 and Comparative Examples 1-2 of this invention are shown below. Figure 6 The hydrogen temperature-programmed reduction diagrams are shown for the catalysts prepared in Examples 1-2 and Comparative Examples 1-2 of this invention. Detailed Implementation

[0023] The following will provide examples and a more comprehensive description of the technical solutions in this invention, including but not limited to the embodiments described herein. Other implementations derived from the embodiments of this invention without inventive step are all within the scope of protection of this invention.

[0024] The numerical values ​​described in the embodiments of this invention are approximate values, not absolutely precise values. Within the allowable range of experimental errors and operating conditions, the scope of protection of this invention covers all values ​​within this error range, and is not limited to the specific values ​​listed in the embodiments. Unless otherwise expressly defined, the definitions of all technical and scientific terms used in this document follow the standard meanings commonly understood by those skilled in the art. The terminology used in this document is only used to describe specific implementation methods and does not constitute a limitation on the scope of protection of this invention.

[0025] This invention proposes a nickel foam-supported silver-cobalt-based monolithic catalyst, its preparation method, and its application. This invention uses AgNO3 and hexadecyltrimethylammonium bromide as Ag species introducers and structure modifiers. The Br in hexadecyltrimethylammonium bromide... - Can be used with Ag + The combination of AgBr precursors facilitates the uniform anchoring of Ag species on the catalyst surface; at the same time, hexadecyltrimethylammonium bromide, with its surfactant properties, regulates the interfacial microenvironment, promoting catalyst morphology control and active site construction.

[0026] Example 1: Preparation of the catalyst Co-Ag4 / NF (1) Cut the nickel foam (NF) into 2cm×3cm pieces, then immerse it in 0.1mol / L HCl solution and sonicate for 10min to remove the surface oxide layer. Then, sonicate it for 5min each with anhydrous ethanol and distilled water, and dry it to obtain clean NF. Then, dissolve 8mmol of 2-methylimidazole in 30mL of deionized water and stir for 10min to form a transparent solution. Place one piece of the treated NF into the 2-methylimidazole solution and sonicate for 30min to obtain the NF carrier, which is then taken out for use. (2) 13.6 mg AgNO3, 0.582 g Co(NO3)2·6H2O, 0.6 g urea, and 0.3 g hexadecyltrimethylammonium bromide were dissolved in 40 mL of deionized water and stirred at room temperature to form a homogeneous solution A. The NF support treated with 2-methylimidazole solution was placed in solution A and then transferred to a high-pressure reactor with a 100 mL polytetrafluoroethylene liner. The reactor was hydrothermally reacted at 120 °C for 12 h. After the reactor cooled to room temperature, the material was removed, washed 5 times with deionized water, and then dried in an oven at 60 °C for 12 h. Finally, the material was calcined in air at 500 °C for 3 h to obtain the Co-Ag4 / NF catalyst.

[0027] Example 2: Preparation of the catalyst Co-Ag2 / NF (1) Cut the nickel foam (NF) into 2cm×3cm pieces, then immerse it in 0.1mol / L HCl solution and sonicate for 10min to remove the surface oxide layer. Then, sonicate it for 5min each with anhydrous ethanol and distilled water, and dry it to obtain clean NF. Dissolve 8mmol of 2-methylimidazole in 30mL of deionized water and stir for 10min to form a transparent solution. Place one piece of the treated NF into the 2-methylimidazole solution and sonicate for 30min to obtain the NF carrier, which is then taken out for use. (2) 6.8 mg AgNO3, 0.582 g Co(NO3)2·6H2O, 0.6 g urea, and 0.3 g hexadecyltrimethylammonium bromide were dissolved in 40 mL of deionized water and stirred at room temperature to form a homogeneous solution A. The NF support treated with 2-methylimidazole solution was placed in solution A and then transferred to a high-pressure reactor with a 100 mL polytetrafluoroethylene liner. The reactor was hydrothermally reacted at 120 °C for 12 h. After the reactor cooled to room temperature, the material was removed, washed 5 times with deionized water, and then dried in an oven at 60 °C for 12 h. Finally, the material was calcined in air at 500 °C for 3 h to obtain the Co-Ag2 / NF catalyst.

[0028] Comparative Example 1: Preparation of the catalyst Co3O4 / NF (1) First, cut the nickel foam (NF) into 2cm×3cm pieces, then immerse it in 0.1mol / L HCl solution and sonicate for 10min to remove the surface oxide layer. Then, sonicate it for 5min each with anhydrous ethanol and distilled water, and dry it to obtain clean NF. Then, dissolve 8mmol of 2-methylimidazole in 30mL of deionized water and stir for 10min to form a transparent solution. Place one piece of the treated NF into the 2-methylimidazole solution and sonicate for 30min to obtain the NF carrier, which is then taken out for use. (2) 0.582 g Co(NO3)2·6H2O, 0.6 g urea, and 0.3 g hexadecyltrimethylammonium bromide were dissolved in 40 mL of deionized water and stirred at room temperature to form a homogeneous solution A. The NF support treated with 2-methylimidazole solution was placed in solution A and then transferred to a high-pressure reactor with a 100 mL polytetrafluoroethylene liner. The reactor was hydrothermally reacted at 120 °C for 12 h. After the reactor cooled to room temperature, the material was removed, washed 5 times with deionized water, and then dried in an oven at 60 °C for 12 h. Finally, the material was calcined in air at 500 °C for 3 h to obtain the Co3O4 / NF catalyst.

[0029] Comparative Example 2: Preparation of the catalyst Co-Ag6 / NF (1) Cut the nickel foam (NF) into 2cm×3cm pieces, then immerse it in 0.1mol / L HCl solution and sonicate for 10min to remove the surface oxide layer. Then, sonicate it for 5min each with anhydrous ethanol and distilled water, and dry it to obtain clean NF. Then, dissolve 8mmol of 2-methylimidazole in 30mL of deionized water and stir for 10min to form a transparent solution. Place one piece of the treated NF into the 2-methylimidazole solution and sonicate for 30min to obtain the NF carrier, which is then taken out for use. (2) 20.4 mg AgNO3, 0.582 g Co(NO3)2·6H2O, 0.6 g urea, and 0.3 g hexadecyltrimethylammonium bromide were dissolved in 40 mL of deionized water and stirred at room temperature to form a homogeneous solution A. The NF support treated with 2-methylimidazole solution was placed in solution A and then transferred to a high-pressure reactor with a 100 mL polytetrafluoroethylene liner. The reactor was hydrothermally reacted at 120 °C for 12 h. After the reactor cooled to room temperature, the material was removed, washed 5 times with deionized water, and then dried in an oven at 60 °C for 12 h. Finally, the material was calcined in air at 500 °C for 3 h to obtain the Co-Ag6 / NF catalyst.

[0030] Comparative Example 3: Preparation of the catalyst Co3O4 / NF-N (1) First, cut the nickel foam (NF) into 2cm×3cm pieces, then immerse it in 0.1mol / L HCl solution and sonicate for 10min to remove the surface oxide layer. Then, sonicate it for 5min each with anhydrous ethanol and distilled water, and dry it to obtain clean NF. Then, dissolve 8mmol of 2-methylimidazole in 30mL of deionized water and stir for 10min to form a transparent solution. Place one piece of the treated NF into the 2-methylimidazole solution and sonicate for 30min to obtain the NF carrier, which is then taken out for use. (2) 0.582 g Co(NO3)2·6H2O and 0.6 g urea were dissolved together in 40 mL of deionized water and stirred evenly at room temperature to form a homogeneous solution A. The NF support treated with 2-methylimidazole solution was placed in solution A and then transferred to a high-pressure reactor with a 100 mL polytetrafluoroethylene liner. The reactor was hydrothermally reacted at 120 °C for 12 h. After the reactor cooled to room temperature, the material was removed, washed 5 times with deionized water, and then dried in an oven at 60 °C for 12 h. Finally, the material was calcined in air at 500 °C for 3 h to obtain the Co3O4 / NF-N catalyst.

[0031] Comparative Example 4: Preparation of the catalyst Co-Ag4 / NF-N (1) First, cut the nickel foam (NF) into 2cm×3cm pieces, then immerse it in 0.1mol / L HCl solution and sonicate for 10min to remove the surface oxide layer. Then, sonicate it for 5min each with anhydrous ethanol and distilled water, and dry it to obtain clean NF. Then, dissolve 8mmol of 2-methylimidazole in 30mL of deionized water and stir for 10min to form a transparent solution. Place one piece of the treated NF into the 2-methylimidazole solution and sonicate for 30min to obtain the NF carrier, which is then taken out for use. (2) 13.6 mg AgNO3, 0.582 g Co(NO3)2·6H2O and 0.6 g urea were dissolved together in 40 mL of deionized water and stirred at room temperature to form a homogeneous solution A. The NF support treated with 2-methylimidazole solution was placed in solution A and then transferred to a high-pressure reactor with a 100 mL polytetrafluoroethylene liner. The reactor was hydrothermally reacted at 120 °C for 12 h. After the reactor cooled to room temperature, the material was removed, washed 5 times with deionized water, and then dried in an oven at 60 °C for 12 h. Finally, the material was calcined in air at 500 °C for 3 h to obtain the Co-Ag4 / NF-N catalyst.

[0032] Catalyst performance evaluation: The performance of the catalysts used in Examples 1-2 and Comparative Examples 1-4 for catalytic oxidation of benzene was evaluated. The test methods and conditions are as follows: The specific performance evaluation conditions were as follows: 0.1 g of the catalysts prepared in the examples and comparative examples were weighed out respectively, and the samples were placed in a continuous flow fixed-bed quartz tube reactor to test their benzene catalytic oxidation performance. The reaction gas flow consisted of 1000 ppm benzene, 20% O2 and N2 (equilibrium), with a total gas flow rate of 100 mL / min and a space velocity controlled at 60000 mL / g / h. The performance evaluation results of the catalysts in the examples and comparative examples are shown in Table 1. Table 1. Performance Comparison of Catalytic Oxidation of Benzene by Catalysts in Examples and Comparative Examples

[0033] As shown in Table 1, the performance comparison of Examples 1, 2, and Comparative Example 2 reveals that the catalyst activity first increases and then decreases with increasing Ag content, indicating that there is an optimal Ag loading. Appropriate Ag content is beneficial for the formation and utilization of active sites, while excessive Ag introduction leads to Ag species aggregation and obscuring some active sites, thus inhibiting the catalytic reaction. Furthermore, compared to Example 1, Comparative Example 4, synthesized without the addition of hexadecyltrimethylammonium bromide, exhibits significantly reduced activity. Similarly, Comparative Example 3, without the addition of hexadecyltrimethylammonium bromide, also shows a trend of performance degradation compared to Comparative Example 1, further demonstrating the important role of hexadecyltrimethylammonium bromide in catalyst structure construction and performance improvement. In summary, reasonable control of Ag content and the introduction of hexadecyltrimethylammonium bromide can jointly promote the improvement of catalyst activity, indicating a synergistic effect between the two in catalyst performance regulation.

[0034] Among them, thanks to the synergistic regulation of appropriate amounts of Ag and hexadecyltrimethylammonium bromide, Example 1 exhibited the best benzene catalytic oxidation performance under the conditions of benzene concentration of 1000 ppm and space velocity of 60000 mL / g / h, with its T 50 and T 90 The temperatures were as low as 228°C and 244°C, respectively.

[0035] The following preferred embodiment 1 (catalysts within the scope of protection of this application have similar technical effects and will not be repeated here) underwent stability and water resistance tests, and the results are shown in [reference to relevant documentation]. Figure 1 and Figure 2 .

[0036] See Figure 1 The Co-Ag4 / NF catalyst prepared in Example 1 was able to react with T in a gas stream containing 1000 ppm benzene and a space velocity of 60000 mL / g / h. 90 After 50 hours of continuous benzene removal, there was no significant decrease in activity, demonstrating excellent long-term operational stability.

[0037] See Figure 2 The Co-Ag4 / NF catalyst prepared in Example 1 can maintain a benzene conversion rate of nearly 90% in gas streams containing 1.5 vol% and 3 vol% water vapor, and its activity quickly recovers to the initial level after the water vapor is stopped, indicating that the catalyst of Example 1 has excellent water resistance.

[0038] See Figure 3As can be seen from the X-ray diffraction patterns of Examples 1-2 and Comparative Examples 1-2, all catalysts exhibit diffraction peaks attributable to cobalt tetroxide (2θ=37.2°, XRD standard card PDF number 43-1003), NF support (XRD standard card PDF number 04-0850), and nickel oxide (XRD standard card PDF number 47-1049). Comparing Examples 1, 2, and Comparative Example 2, a diffraction peak at 2θ=37.9° at Comparative Example 2, belonging to the (111) crystal plane of Ag, appears. This indicates that when the Ag introduction amount is 2 at% and 4 at%, Ag exists in an atomically dispersed form on the catalyst surface. However, when the Ag introduction amount reaches 6 at%, some Ag species may agglomerate, forming tiny Ag nanocrystals. This result corroborates the aforementioned pattern of catalytic activity first increasing and then decreasing, proving that Ag nanoparticle agglomeration is an important cause of catalytic performance degradation under high introduction amounts.

[0039] See Figure 4 As observed in the scanning electron microscope images of Examples 1-2 and Comparative Examples 1-2 (a1-a4), the three-dimensional network structure of the NF support was preserved in all samples, indicating that the hydrothermal in-situ growth method did not significantly affect the overall morphology of the substrate. Hexadecyltrimethylammonium bromide-assisted Ag loading is a key factor in regulating the crystal growth behavior and final microstructure of cobalt tetroxide. Specifically, as... Figure 4 b1 and Figure 4 c1, without the introduction of Ag, Co3O4 consists of uniformly sized nanoparticles that cross-link with each other to form a continuous network structure. On the surface of Example 2 ( Figure 4 b2 and Figure 4 c2), the introduction of a small amount of Ag can induce the preferential growth of Co3O4 along the one-dimensional direction, thereby forming a uniformly distributed nanoribbon structure. When the Ag loading is moderate, the Ag species play a more effective morphology guiding role in the crystal growth process, inhibiting the continued free one-dimensional growth of the surface crystals in Example 1, and instead inducing them to bend and self-assemble in a specific orientation, ultimately forming an open porous roll-like three-dimensional structure (c2). Figure 4 b3 and Figure 4 c3), this structure is generally advantageous for exposing active sites and provides an efficient channel for the diffusion and mass transfer of reactants and products, making it an ideal morphology for improving catalytic performance. From the morphology of Comparative Example 2, we can obtain ( Figure 4 b4 and Figure 5 (c4) Excessive Ag loading can cause Ag species to aggregate, thereby altering the crystallization environment of cobalt tetroxide, disrupting the ordered self-assembly process, and instead promoting the formation of dense, smooth cubic block structures on the catalyst surface. This structure typically clogs pores, hindering the contact and transport of reactants.

[0040] SeeFigure 6 As observed from the electron paramagnetic resonance spectra of Examples 1-2 and Comparative Examples 1-2, Example 1 showed a stronger signal value (g=2.003), which indicates that it has more oxygen vacancies, which is beneficial to the activation of gaseous oxygen and ultimately improves the low-temperature activity of the catalyst.

[0041] See ​ Based on the hydrogen temperature-programmed reduction results of Examples 1-2 and Comparative Examples 1-2, the reduction peak temperature of Example 1 was significantly lower than that of other catalysts. This means that the lattice oxygen in the catalyst is more easily activated and migrated, and has better low-temperature redox properties.

[0042] In summary, the Co-Ag4 / NF catalyst prepared in this invention exhibits atomically uniform Ag dispersion without particle agglomeration, and forms an open, porous, three-dimensional spiral structure that fully exposes catalytic active sites, efficiently promoting mass transfer and diffusion of reactants. Compared to other samples, it has a richer number of oxygen vacancies, stronger lattice oxygen activation and migration capabilities, and particularly superior low-temperature redox performance. Furthermore, this catalyst possesses excellent structural stability, enabling long-term stable catalysis, and exhibits outstanding water resistance.

[0043] The above description is merely a preferred embodiment of the present invention, and the scope of protection of the present invention is not limited to the above embodiments. For those skilled in the art, any modifications, equivalent substitutions, or improvements made without departing from the technical concept of the present invention should be included within the scope of protection of the present invention.

Claims

1. A method for preparing a nickel foam-supported silver-cobalt-based monolithic catalyst, characterized in that the steps include... include: (1) Remove the surface oxide layer from the cut nickel foam, then perform ultrasonic cleaning to obtain clean nickel foam, and dry it for later use; put the dried nickel foam into 2-methylimidazole solution and perform ultrasonic treatment to obtain nickel foam carrier. (2) AgNO3, Co(NO3)2·6H2O, urea and hexadecyltrimethylammonium bromide are dissolved together in deionized water and stirred at room temperature to form a homogeneous solution. The nickel foam support obtained in step (1) is placed in the homogeneous solution and subjected to hydrothermal reaction. After cooling to room temperature, a nickel foam-supported silver cobalt-based composite material is obtained. After washing with deionized water and drying, it is finally calcined in air atmosphere to obtain a nickel foam-supported silver cobalt-based monolithic catalyst.

2. The preparation method of the nickel foam-supported silver-cobalt based monolithic catalyst according to claim 1, characterized in that, In step (1), the nickel foam is cut to a size of 6-8 cm. 2 The surface oxide layer was removed using an HCl solution with a concentration of 0.1–0.3 mol / L, and the ultrasonic cleaning time was 5–15 min.

3. The method for preparing the nickel foam-supported silver-cobalt-based monolithic catalyst according to claim 1, characterized in that, In step (1), the 2-methylimidazole solution is a transparent solution obtained by stirring and dissolving for 5 to 15 minutes, and its concentration is 0.1 to 0.5 mol / L.

4. The method for preparing the nickel foam-supported silver-cobalt-based monolithic catalyst according to claim 1, characterized in that, In step (1), the ultrasonic treatment time is 20 to 40 minutes.

5. The method for preparing the nickel foam-supported silver-cobalt-based monolithic catalyst according to claim 1, characterized in that, In step (2), the molar percentage of Ag / Co is 2-4%, the amount of Co(NO3)2·6H2O is 2-6 mmol, the amount of urea is 0.01-0.03 mol, and the amount of hexadecyltrimethylammonium bromide is 0.8-1.5 mmol.

6. The method for preparing the nickel foam-supported silver-cobalt-based monolithic catalyst according to claim 1, characterized in that, In step (2), the hydrothermal reaction temperature is 100-150℃ and the hydrothermal reaction time is 8-16h; the number of times of washing with deionized water is at least 3; the drying temperature is 60-80℃ and the drying time is 10-15h; the calcination temperature is 300-700℃ and the calcination time is 2-6h.

7. A nickel foam-supported silver-cobalt-based monolithic catalyst prepared by the preparation method according to any one of claims 1 to 6, characterized in that, include: A three-dimensional porous nickel foam carrier and a silver-doped cobalt tetroxide active layer loaded on the surface of the nickel foam carrier; wherein the active layer has an open porous roll-shaped three-dimensional structure formed by the assembly of rolled nanosheets.

8. The use of a catalyst prepared by the method according to any one of claims 1 to 6 or the catalyst according to claim 7 in the thermocatalytic oxidation of volatile organic compounds.

9. The application of a catalyst prepared by any one of claims 1 to 6 or the catalyst as described in claim 7 in the thermocatalytic oxidation of benzene.

Citation Information

Patent Citations

  • Quenching silver-loaded cobalt-based monolithic catalyst as well as preparation method and application thereof

    CN119281352A